2006
DOI: 10.1001/archsurg.141.7.659
|View full text |Cite
|
Sign up to set email alerts
|

Initial Clinical Evaluation of a Handheld Device for Detecting Retained Surgical Gauze Sponges Using Radiofrequency Identification Technology

Abstract: Hypothesis: A handheld wand-scanning device (1.5 lb, battery powered, 10ϫ10ϫ 1.5 in) has been developed to detect commonly used surgical gauze sponges, which have been tagged with a radiofrequency identification (RFID) chip. We tested the hypothesis that this wand device has a successful detection rate of 100%, with 100% specificity and 100% sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
132
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(139 citation statements)
references
References 13 publications
2
132
1
4
Order By: Relevance
“…There are many reports of RFID use in healthcare in general. [2][3][4][5][6][7][8][9] At Nemours Children's Hospital in Orlando, Florida, RFID supports the concept of a hospital having a single logistics center that monitors and runs operations. Interest in RFID technology seems high, as it can be applied beyond asset location to temperature and humidity monitoring and improving clinician workflow.…”
Section: Discussionmentioning
confidence: 94%
“…There are many reports of RFID use in healthcare in general. [2][3][4][5][6][7][8][9] At Nemours Children's Hospital in Orlando, Florida, RFID supports the concept of a hospital having a single logistics center that monitors and runs operations. Interest in RFID technology seems high, as it can be applied beyond asset location to temperature and humidity monitoring and improving clinician workflow.…”
Section: Discussionmentioning
confidence: 94%
“…There is another study comparing traditional counting method with computerassisted counting of sponges using barcodes in a randomized control trial with 298 patients. Results of this study demonstrated that the barcode system is associated with significantly more counting discrepancies compared to customary system (13,17,18).…”
mentioning
confidence: 76%
“…Current protocols for preventing the retention of foreign objects after surgery are summarized in Table 1. [2][3][4][9][10][11][12] In operations with a high risk of error, it has been suggested that universal radiographic screening be done regardless of the surgical count.…”
Section: Risk Reductionmentioning
confidence: 99%
“…• Susceptible to electronic interference, mechanical failure and user error 11,12 Note: CT = computed tomography.…”
Section: Ct Scanningmentioning
confidence: 99%